Ultrasound Collaboration across Europe: An EFSUMB success story in politically troubled times? - Sidhu, P. S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
In these days of political vagueness, to use a kinder term, although many would describe the situation as turmoil, in Europe, there are success stories to be lauded. Notwithstanding the direction individual countries choose in relation to closer or not so close co-operation in Europe and the direction the political agenda will travel over the next few years, I believe science and in particular medicine has benefited enormously form close co-operation across the European Union and with colleagues outside this political and trading block of nations. Ultrasound within the community of medical scientists and clinicians is a unique imaging tool that links various disparate specialities that collaborate little in any sphere other than imaging with the tool of sonography. An umbrella organization that allows co-operation between the medical specialities, and brings basic scientist under one roof to co-operate closely is undoubted of benefit ultimately with the customer, in this case the patient.The European Federation of Societies of Ultrasound in Medicine and Biology (EFSUMB) has over the last few years in particular achieved this unique position of bringing together peoples from across the European nation in collaboration in numerous projects, using skilled expertise from different nations to forge the common aim of advancing the practice of ultrasound as applied to biology and medicine. The success of this collaboration is demonstrated by the number of guidelines issued by EFSUMB over the years, well received across the globe and respected by numerous citations in the literature. The main areas of expertise has been in the guidelines associated with contrast ultrasound 12 and elastography 34, but also with guidelines pertaining to interventional ultrasound 5, student education 6 and recently contrast ultrasound in paediatric practice 7. More guidelines are planned, with input from many different experts from societies within the family of EFSUMB. These guidelines set the benchmark for ultrasound practice across the world and are often mimicked by others.This collaboration and continued output is important. With the recent Food and Drug Administration (United States of America) approval of the use of an ultrasound contrast agent for focal liver lesions, a worldwide change of practice will occur. This was achieved without a clinical trial in children, a previously unheard of occurrence and solely based on the experience, expertise and pioneering activities of investigators in Europe, many embolden by the support of colleagues across Europe sharing experience through EFSUMB. The lead in establishing ultrasound elastography has also originated in Europe with close and strong collaboration to produce guidelines, again pioneering the application of elastography to clinical situations. More important guidelines are on the horizon dealing with liver elastography, non-hepatic contrast ultrasound and gastrointestinal ultrasound.This success translates to the success of the journal, Ultraschall in der Medizine/European Journal of Ultrasound, with a rising impact factor, rising manuscript submissions and limited space. Where can authors in Europe publish their innovative research to continue this journey? This is one of the pitfalls of the European success story, perhaps in time we can resolve this by increasing on-line papers, increasing page numbers in the journal etc. but this is a problem of the publication industry in general.The most important element from this success story has to be the success of collaboration across the borders of the European nations, and this has also to be the success of the European Union in achieving this close scientific and medical environment. The potential adverse effect this will have on the scientific collaboration in the United Kingdom, my own area of professional activity, following a vote to re-consider membership of the European Union, is largely unpredictable. Nevertheless this is of great concern to many of us in the United Kingdom that an opportunity may be lost, with new generations of medical doctors no longer able to travel and work freely across Europe, bring ideas with them, and returning with new ways to practice. I have undoubtedly benefited from the numerous overseas doctors who have come to work in my own department over many years. My own hope is that the seeds of collaboration are so embedded in our work routine that we in the scientific and medical community have now forever achieved collaboration as a second nature which will be only strengthened with any political fallout across Europe. The time for continuing support for an umbrella organization for the advancement of medicine and biology in ultrasound has never been greater.